Character education in the Indonesian National Curriculum : an evaluation of senior high school's English textbooks - Eka (Kulliyyah of Education, International Islamic University Malaysia, 2017)
This research sought to investigate the presence of character education elements in the senior high school's English textbooks that are written based on the National Curriculum 2013 and published by the Indonesian Ministry of Education and Culture in 2014. Three new English textbooks are analysed and also compared to the three selected old-textbooks which were published in 2008. According to the Ministry of Education and Culture, Indonesia, there are four main character configurations in the National Framework for Character Education 2010. Those character development configurations are a) spiritual and emotional development, b) intellectual development, c) physical and kinesthetic development, and d) affective and creativity development. The eighteen values that are identified by the General Directory of Education and Culture are also used as the secondary criteria. In this research, the researcher employed Qualitative Descriptive Analysis and content analysis techniques. In general, the study follows White and Marsh's (2006) procedures of analysis namely formulating research questions, sampling, coding, and analysing. Critical analysis is also used to discuss the implications from the findings of the study. The findings indicate that the three new English textbooks contain the eighteen values which are promoted more deliberately (by 418 chunked texts) compared to the three old English textbooks (by 170 chunked texts). The top-five values promoted in the new English textbooks are “socially concerned, environmentally aware, peace loving, hardworking, and religious values; and for the old textbooks are environmentally aware, responsible, disciplined, fond of reading, and hardworking” values. The eighteen values promoted in the contents of English textbooks indicate the presence of three character development configurations namely a) spiritual and emotional development, b) intellectual development, c) affective and creativity development. Meanwhile, physical and kinesthetic development configurations were not found in the English texts. The findings also implicate that the English textbooks equipping 2013 curriculum contain character education elements and hence supports character education implementation. The study suggests that English teachers promote the identified eighteen values in delivering the English textbooks' contents so that they can instil the values confidently and deliberately in students.